"Despite the Odds": Unpacking the Politics of Black Resilience Neoliberalism. (February 2019) - Clay, Kevin L.
Through sustained ethnographic field work that inquired into youth participatory action researchers' political identity development, I identified a politicized discourse engaged by youth during their early stages of action research that I have termed Black resilience neoliberalism (BRN). This study explicates BRN theory, tracing its connection to policy discourses related to Black youth and schools and exploring the ways its tenets are revealed in Black youth action researchers' reflections on race/racism, inequality, and social change. I argue that BRN is both a conspicuous and an inconspicuous thread of neoliberal discourse and logic, which hides in plain sight as empowerment; however, it is entangled with the project of hegemony. To that end, destabilizing the legitimization of BRN is crucial to reconstituting empowerment.